P-161 The role that endogenous oleic acid synthesis plays in cell proliferation and expression of folliculogenesis markers in ovarian granulosa cells. (30th June 2022) - Fayezi, S; Lange, C; Jauckus, J; Rehnitz, J; Nguyen, X.P; Strowitzki, T; Germeyer, A
Abstract: Study question: Does a deficiency of endogenous oleic acid synthesis affect cell proliferation and the expression of folliculogenesis markers in the ovarian granulosa cell line COV434? Summary answer: Endogenous oleic acid synthesis supports cell proliferation and the expression of folliculogenesis markers, which are possibly linked to oocyte maturation. What is known already: The endogenous synthesis of the monounsaturated fatty acid oleic acid from saturated fatty acids is catalysed by stearoyl-coenzyme A desaturase (SCD). Previous studies have suggested that lipid monounsaturation may promote steroidogenesis and oocyte development. However, the potential role of endogenous oleic acid synthesis in folliculogenesis remains virtually unexplored. Autophagy related 14 (ATG14), growth differentiation factor 9 (GDF9), signal transducer and activator of transcription 3 (STAT3) and forkhead box protein O1 (FOXO1) play essential roles in follicular development via promotion of proliferation and maturation of ovarian granulosa cells. Study design, size, duration: Immortalized granulosa cells (COV434) were cultured, treated with a specific SCD inhibitor (SCDi) and supplemented with or without oleic acid for 48 h. The cells were cultured for a further 24 h in normal media. The cell culture medium was then discarded and the cells were washed before a viability assay or RNA extraction was performed. RNA extraction was followed by cDNA synthesis and real-time PCR assessment. All experiments were conducted three times in duplicate. Participants/materials, setting, methods: Cell proliferation was determined using a crystal violet viability assay. The expression of the folliculogenesis markers ATG14, GDF9, STAT3 and FOXO1 was analysed using TaqMan real-time PCR. Main results and the role of chance: The cell proliferation rate was considerably lower in SCDi-treated cells compared to untreated control cells (-50%, p < 0.01), and the effect was fully recovered by adding oleic acid to the SCDi-conditioned cells. SCDi treatment led to significant decreases in ATG14 (-90%), GDF9 (-86%), STAT3 (-62%) and FOXO1 (-93%) ( p < 0.01) compared with the baseline control levels. Oleic acid was found to partially, but significantly, suppress the inhibitory effect of SCDi on the expression of the folliculogenesis markers. The rescue effect of oleic acid was significantly stronger after an extended culture time following SCDi treatment. Limitations, reasons for caution: Further studies need to be performed, possibly with primary cell cultures, to confirm these effects. Wider implications of the findings: The involvement of the endogenous synthesis of oleic acid in ovarian granulosa cell functionality is relevant to reproductive disorders that affect oogenesis. Trial registration number: not applicable